Visibility optimization of satellite constellations using a hybrid method - Han, Chao; Bai, Shengzhou; Zhang, Sihang; Wang, Xinwei; Wang, Xiaohui (Acta astronautica, 2019)
For the visibility optimization problem of satellite constellations, this paper presents an efficient hybrid optimization method taking multiple constraints into account. To reduce the time needed for the optimization, the satellite constellation is assumed to have a specific configuration. The optimization includes two steps. The first step searches for optima over a large scale, while the second step is designed to obtain the accurate optimal solution based on the result of the first-step optimization. Based on the analysis of the coverage performance function, a linear adaptive population method is proposed for the first step. When compared with the traditional optimization method, calculation time can be efficiently reduced while ensuring an accurate optimization. Several numerical simulations are conducted for validation. It proves to be a practical choice for engineering applications. •Different types of satellite load sensors and different coverage performance indices are considered.•Constraints of double- or more-level coverage are discussed.•The trend of the number of local maximum points of one-level coverage to the ground point are analyzed.•A novel hybrid two-step optimization method is proposed.